El Paso Phase Obsidian Procurement in Southern New Mexico: Implications for Jornada Mogollon Regional Interaction and Exchange. Issue 3 (3rd July 2017) - Dolan, Sean G.; Miller, Myles R.; Shackley, M. Steven; Corl, Kristin
Abstract : Archaeologists rarely discuss obsidian procurement for the Jornada Mogollon region, but studies indicate groups overwhelmingly used obsidian that can be collected from Rio Grande gravels in southern New Mexico. Obsidian artifacts from two El Paso phase sites, Cottonwood Spring Pueblo and Madera Quemada Pueblo, were sourced using EDXRF spectrometry to determine: (1) is there evidence for non-Rio Grande gravel obsidian use, (2) is there a difference between the sites, and (3) how do these sourcing results compare with contemporaneous sites in the Casas Grandes area? This study has implications for regional interaction and exchange as the results validate the high frequency of Cerro Toledo Rhyolite obsidian in assemblages, but non-Rio Grande gravel sources were also used including Mule Creek projectile points. People at both sites used similar sources, with a few noted exceptions. Furthermore, groups in the Jornada Mogollon and Casas Grandes regions utilized dramatically different sources.